PARENTING PRACTICES SELF-EFFICACY AND PEER SUPPORT ON RESILIENCE IN ADOLESCENTS - Suci Yolianda Utami; Dwi Hastuti; Yulina Eva Riany (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2025)
The family is the primary environment that shapes a child's physical and psychological development. However, inappropriate family conditions or structures can be a source of stress that impacts adolescent resilience in facing life's challenges. This study aims to analyse the influence of parenting practices, self-efficacy, and peer support on the resilience of adolescents from intact and divorced families. The population in this study were high school students in Bogor City, with 240 respondents consisting of 180 adolescents from intact families and 60 from divorced families. The results showed that there were significant differences in parenting practices and self-efficacy between adolescents from intact and divorced families. Self-efficacy and peer support had a positive and significant effect on adolescent resilience. In addition, parenting practices also contributed to building resilience, although the effect was smaller. These findings emphasise the important role of parents and the social environment in supporting the psychological resilience of adolescents in both intact and divorced families. Family conditions or family structure have a significant impact on parenting practices, self-efficacy, and resilience in adolescents. Adolescents from intact families receive more positive parenting patterns, such as support, warmth, and high responsiveness from their parents. These parenting patterns impact high self-efficacy, especially in academic and emotional aspects. Conversely, adolescents from divorced families show lower self-efficacy, although self-acceptance in resilience is actually higher. Peer support was found to play a significant role in strengthening self-efficacy and resilience, without significant differences between family backgrounds. This indicates that peers are a relatively stable source of support for adolescents across various family conditions. Correlation and regression tests indicate that parenting practices, self-efficacy, and peer support have a positive and significant influence on adolescent resilience. These findings also indicate that self-efficacy is the most powerful factor in shaping resilience, especially for adolescents from divorced families. Negative parenting practices such as excessive punishment can weaken adolescent self-efficacy and resilience. Therefore, social support and adaptive parenting are crucial in building overall adolescent resilience. Key words: peer support, self-efficacy, intact families, parenting practices, resilience